An Electrochemical Approach for the Direct Synthesis of 3, 5‐Disubstituted 1, 2, 4‐Triazoles from Nitriles and Hydrazides. Issue 13 (1st April 2020) - Singh, Manjula; Kant Sharma, Laxmi; Dubey, Rahul; Kumar Patel, Manoj; Prakash, Ved; Krishna Pal Singh, Rana
Abstract : A highly facile, efficient and environmentally friendly protocol for the first electrochemical synthesis of 3, 5‐disubstituted 1, 2, 4‐triazoles from nitriles and hydrazides is reported. The reaction efficiency involves anodic oxidation and cathodic reduction, and has a good functional group tolerance. This synthetic approach is operationally simple and gives good to excellent yields under mild conditions in a one‐pot procedure. It utilizes KI as the redox catalyst under external oxidant‐free conditions.